“Super Responder” of Percutaneous Bicaval Valve Implantation for Severe Tricuspid Regurgitation: A Case Report - Ignatius Yansen; Bayushi Eka Putra; Muhammad Yamin; Simon Salim (Acta Medica Indonesiana, 2025)
Tricuspid Regurgitation (TR) surgical treatment is associated to high operative mortality, suboptimal long-term survival, and frequent TR recurrence after repair, especially in the elderly. This case report highlights our early experience of TricValve implantation in Indonesia, conducted on a 72-year-old male patient with severe tricuspid regurgitation and advanced right ventricular dysfunction. In this context, the TricValve system offers a promising, less invasive alternative. Despite previous pharmacological management, our patient had been readmitted multiple times due to refractory right heart failure. One month post-TricValve implantation, he showed significant symptomatic relief and stable cardiac function as evidenced by echocardiographic measurements. This case underscores the potential utility of the TricValve system in providing an effective, lower-risk treatment option for patients not suited for traditional surgical intervention.